2007
DOI: 10.1308/003588407x205440
|View full text |Cite
|
Sign up to set email alerts
|

Theatre Shoes — A Link in the Common Pathway of Postoperative Wound Infection?

Abstract: INTRODUCTION Operating department staff are usually required to wear dedicated theatre shoes whilst in the theatre area but there is little evidence to support the beneficial use of theatre shoes.PATIENTS AND METHODS We performed a study to assess the level of bacterial contamination of theatre shoes at the beginning and end of a working day, and compared the results with outdoor footwear. RESULTS We found the presence of pathogenic bacterial species responsible for postoperative wound infection on all shoe g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Whether this was related to fallout from the shoes or increased human activity was not analyzed. Similar to Amirfeyz et al, 136 Copp et el 139 found increased rates of bacterial transfer to the OR floor from street shoes than from designated theatre-only shoes or shoes with covers. Again, the relationship of this to SSIs was not studied.…”
Section: Studies Concerning Gown Use and Bacterial Contaminationmentioning
confidence: 64%
See 3 more Smart Citations
“…Whether this was related to fallout from the shoes or increased human activity was not analyzed. Similar to Amirfeyz et al, 136 Copp et el 139 found increased rates of bacterial transfer to the OR floor from street shoes than from designated theatre-only shoes or shoes with covers. Again, the relationship of this to SSIs was not studied.…”
Section: Studies Concerning Gown Use and Bacterial Contaminationmentioning
confidence: 64%
“…Modern ORs with high air turnover rates and laminar flow air systems supposedly minimize the chances of floor redispersal, although this has never been proven. 136 Clean appearance of shoes has been shown to be an unreliable method of determining bacterial contamination. 137 Many hospitals have no set cleaning protocols regarding shoes worn in the operatory, even if dedicated footwear is required.…”
Section: Studies Concerning Gown Use and Bacterial Contaminationmentioning
confidence: 99%
See 2 more Smart Citations
“…Redispersed floor bacteria make up a portion of the airborne bacteria concentration as well (Amirfeyz et al 2007). Persson et al (2003) showed these airborne bacteria may be killed by an antiseptic gas before reaching the surgical wound.…”
Section: Introductionmentioning
confidence: 99%